Study on pervious recycled aggregate fiber-reinforced concrete for airfield pavement. Issue 1 (February 2020) - Novak, J; Kohoutkova, A; Chylik, R; Trtik, T
Abstract: For the last several years, the attention has been devoted to the development of eco-friendly construction materials with the aim to reduce the environmental impact of construction. The integral part of this development is to find applications for which the recycled materials could be used efficiently. The presented study deals with the development of recycled aggregate fibre reinforced concrete which is going to be used for an innovative precast concrete pavement system. The system is being developed recently at Czech Technical University in Prague with the aim to provide a system for airfield pavement with rapid construction and recycled material utilization. The investigated material is going to be used for construction of a sub-base course which is underneath a surface course of precast concrete elements. Within the scope of the work, standard laboratory tests were conducted with the aim to observe mechanical properties of recycled aggregate fibre reinforced concrete. The obtained findings showed that the material exhibits ductile behaviour likely due to very long polypropylene fibres used for strengthening concrete matrix. On the contrary, the tested material has low modulus of elasticity in comparison with conventional concrete. Subsequently, the pilot construction of the sub-base course was carried out in order to examine both concrete mixture preparation and concrete course installation in practice. The obtained findings showed that a compaction ratio of the material is about 20%. Moreover, a flat surface of the sub-base course was hard to achieve considering the used manufacturing technology.